Brand gender-bending: The impact of an endorsed brand strategy on consumers' evaluation of gendered mixed-target brands. (30th May 2018) - Azar, Salim L.; Aimé, Isabelle; Ulrich, Isabelle
Abstract : Purpose: Mixed-target brands with strong gender identities, whether it be feminine or masculine, are not always successful at targeting both men and women, particularly in symbolic product categories. While attempting to maximize their sales for both targets, managers often struggle to capitalize on a single brand, and they hesitate between different naming strategies. This paper aims to build on brand gender literature and understand these brands' (i.e. brands targeting both men and women) potential to adopt an endorsed brand strategy rather than a branded house strategy. Design/methodology/approach: The paper uses a before/after experimental design to examine the effect that introducing a gender-incongruent endorsed brand (i.e. feminine endorsed brand name of masculine master brands and masculine endorsed brand name of feminine master brands) can have on consumers' brand attitude. Findings: First, adopting an endorsed brand strategy increases the perceived brand femininity of masculine master brands, but there is no increase in feminine master brands' perceived brand masculinity. Second, this strategy has a negative impact on consumer attitude toward the master brand, with a stronger negative effect for feminine master brands than for masculine master brands, which is mediated by the brand gender perception change. Third, a negative feedback effect on the brand's gender-congruent users is revealed. Research limitations/implications: One limitation of this work is that the focus is on one sole extrinsic brand characteristic (i.e. brand name) in our experimental design, which artificially influences the relative brand name importance for consumers. Moreover, the studies offered a short text to introduce the renaming. This may have made the respondents focus on the brand more than they would have in real-world conditions. Practical implications: This research provides many insights for masculine or feminine mixed-target brands managers in symbolic product categories, as it shows that changing from a branded house strategy to an endorsed brand strategy appears to be unsuccessful in the short run, regardless of master brand's gender. Moreover, the study reveals negative feedback effects on the attitude toward the initial master brand, following its renaming, in the short run. Originality/value: This research provides a warning to managers trying to gender-bend their existing brands because it can lead to brand dilution. It also emphasizes the asymmetrical evaluation of masculine vs feminine master brands, as manipulating a brand's perceived masculinity appears very difficult to do successfully.